Augmenting Reality: (Big‐)Data‐informed Urban Design and Planning. (31st March 2020) - Tunçer, Bige
Abstract: Data‐mining of people's movement around cities and their social media feeds is seen by many as invasive and controlling. Bige Tunçer, founder of Singapore University of Technology and Design's Informed Design Lab, describes how such data and its augmented‐reality projections can be used to facilitate better urban design strategies and understandings.